SAVDO KORXONALARIDA TA’MINOT TIZIMINI LOGISTIKA XIZMATLARI ASOSIDA TAKOMILLASHTIRISH - S.B.Baqoyev (NAZARIY VA AMALIY FANLARDAGI USTUVOR ISLOHOTLAR VA ZAMONAVIY TA'LIMNING INNOVATSION YO'NALISHLARI, 2025)
The sale of goods in wholesale and retail trade is associated with the organization of the supply of goods, ensuring the accuracy of the order parameters and providing additional technological services related to the timely delivery of goods to customers. The use of logistics service throughout the supply chain of all goods helps to form a customer service system and maintain it in working conditions.